Long-Term Protection in Atlantic Salmon (Salmo salar) to Pancreas Disease (PD) Can Be Achieved Through Immunization with Genetically Modified, Live Attenuated Salmonid Alphavirus 3 - Stine Braaen; Øystein Wessel; Håvard Bjørgen; Espen Rimstad (Vaccines)
Background: Pancreas disease (PD) is a serious disease in European salmonid aquaculture caused by salmonid alphavirus (SAV), of which six genotypes (SAV1–6) have been described. The use of inactivated virus and DNA PD vaccines is common in marine salmonid aquaculture and has contributed to a reduction of the occurrence of disease; however, outbreaks are still frequent. Methods: In this study, we compared the long-term protection after immunization of Atlantic salmon (Salmo salar) with three different clones of attenuated infectious SAV3. The clones were made by site-directed mutagenesis targeting the glycoprotein E2 to disrupt the viral attachment and/or nuclear localization signal (NLS) of the capsid protein to disrupt the viral suppression of cellular nuclear-cytosol trafficking. The resulting clones (Clones 1–3) were evaluated after injection of Atlantic salmon for infection dynamics, genetic stability, transmission, and protection against a subsequent SAV3 challenge. Results: Attenuated clones demonstrated reduced virulence, as indicated by lower viral RNA loads, diminished transmission to cohabitant fish, and minimal clinical symptoms compared to the virulent wild-type virus. The clones mutated in both capsid and E2 exhibited the most attenuation, observed as rapid clearing of the infection and showing little transmission, while the clone with glycoprotein E2 mutations displayed greater residual virulence but provided stronger protection, seen as reduced viral loads upon subsequent challenge with SAV3. Despite their attenuation, all viral clones caused significant reductions in weight gain. Conclusions: Despite promising attenuation and protection, this study highlights the trade-offs between virulence and immunogenicity in live vaccine design. Concerns over environmental risks, such as the shedding of genetically modified virus, necessitate further evaluation. Future efforts should optimize vaccine candidates to balance attenuation, immunogenicity, and minimal side effects.